Accounting students' perceptions of effective teaching methods and instructor characteristics: some Malaysian evidence - Abdul Hamid, Fatima; Nik Ahmad, Nik Nazli; Megat Mohd Nor, Putri Nursuad; Mohd. Nor, Anita (Accounting Research Institute (ARI), 2007)
This paper examines accounting students’ perceptions of effective teaching methods and instructor characteristics. The study also explores whetherdifferences in students’ perceptions exist across gender, ethnic origin and prior academic performance. The sample comprises accounting students in two Malaysian universities. The results suggest that students perceive a student-centred approach to teaching as being most effective. The instructor characteristic most valued by students is the instructor’s knowledge. The findings also suggest some differences in perceptions across gender, ethnic origin and prior academic performance. The study has several implications. First, it contributes to the literature on accounting students’ perceptions of effective teaching methods and instructor characteristics. Second, the study provides insights into ways to make the teaching of accounting more effective. Finally, it is hoped that the study will be able to assist in the formulation of guidelines for the effective teaching of accounting.